STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN JUMLAH PESERTA DIDIK BARU MELALUI PROGRAM DI SD ISLAM TERPADU SULTHONIYAH SAMBAS TAHUN AJARAN 2023-2024 - Hesti Purwanti; Rusiadi, Elsa Mulya Karlina (ADISAM PUBLISHER, 2024)
This research was conducted because there is an interesting problem regarding the school at Sulthoniyah Sambas Integrated Islamic Elementary School in increasing the number of new students because this elementary school has just been established and is able to compete with schools that have been established for a long time, both fellow private schools and other schools. country in Sambas Regency. The aim of this research is to determine the planning, implementation and supporting factors inhibiting school principals in increasing the number of new students through the program. The research uses a qualitative approach with a phenomenological type of research. The results of the research are planning by improving the quality of schools by providing superior school programs, conducting observations and comparative studies with other schools, promoting schools on social media by sharing school activities every day, and providing allowances in the form of internet quota to teachers. every month in the context of implementing school promotions. The implementation starts from forming a new student admissions committee (PPDB), monitoring the committee, evaluating each program and good teamwork. Supporting and inhibiting factors are cooperation with kindergarten, and learning guidance (Bimbel), support from students' parents and the community. The inhibiting factors in implementing the program are school facilities or school facilities and infrastructure, inadequate facilities in the form of classroom buildings to increase the student admission quota and minor technical errors made by the committee when registering prospective new students such as errors in names or addresses.